Male and female reproductive success in a threatened Polygynous species: the Strange-tailed Tyrant, Alectrurus risora - Di Giacomo, Adrian Santiago (2011)
The Strange-tailed Tyrant (Alectrurus risora) is an endangered obligate grassland bird that inhabits savannas, wet grasslands and marshes in southern Paraguay and northeastern Argentina. We evaluated the extent of social polygyny, main measures of reproduction (clutch size, hatching success, and chick survival), and factors that influence nest success in this species. We also estimated the reproductive success of females and males by measuring the number and fate of nesting attempts by banded females and the number of females per a male's territory. More than 80% of the males were polygynous. Males defended contiguous territories of 2-2.5 ha that included the territories of up to four females. Females built the nest, incubated the eggs, and brooded and fed the chicks. On average, successful nests fledged 2.3 chicks. Nest survival over the entire cycle was 0.23 and decreased with nest age and time of breeding. Most females made two or three nesting attempts per breeding season and bred in the same area for 2 or 3 consecutive years. In contrast, males rarely were seen in the same area more than 1 year, suggesting sexual differences in mortality. As a result of this, the reproductive succcess of females and males was similar. Our findings indicate that although males are highly polygynous and nest success is low, the high turnover of males in successive breeding seasons and the high probability of females' renesting within and in successive breeding seasons reduce the variance in reproductive success of both sexes.